Pengaruh Model Pembelajaran Ekspositori Terhadap Motivasi Belajar Siswa Kelas X SMK HKBP Swasta Sidikalang 2022/2023 - Masrida Tania Rajagukguk; Damayanti Nababan; Andar Gunawan Pasaribu; Lince R.T. Simamora; Sabar Rudi Sitompul (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The aim of this research is to determine the influence of the Expository Learning Model on the Learning Motivation of Class X Students of SMK HKBP Sidikalang 2022/2023. The method used in this research is a quantitative inferential statistical research method. The population is all 119 class X students of HKBP Sidikalang Vocational School who are Christians. Sampling used random sampling techniques, namely class X with a total of 48 people. Data was collected using a positive closed questionnaire with 36 items. The results of data analysis show that there is a positive and significant influence of the Expository Learning Model on the PAK Learning Motivation of class ,n=48) = 0.284, thus it is known that there is a positive relationship between variable = 1.678, thus there is a significant relationship between variable X and variable Y. c) Test the effect of regression determination (r2) = 15.44%. 2) Influence test: Regression equation test, obtained regression equation Ŷ=37.68+1.31X. Thus Ha is accepted and H0 is rejected. This research concludes that there is a positive and significant influence of the Expository Learning Model on the PAK Learning Motivation of Class In connection with the results of this research, the author provides input for schools to improve and maintain a good and structured Expository learning model so that it can increase student learning motivation.